Challenges of STEM Vocations in Secondary Education - Ayuso, Alba; Merayo, Noemi; Ruiz, Ines; Fernandez, Patricia (IEEE transactions on education, 2022)
Contribution: There is a significant decline in technological vocations despite a huge increase in labor demand for professionals in these sectors. This technology-related problem has become a major concern for governments, organizations, and education systems. Students' motivation toward Science, Technology, Engineering, and Mathematics (STEM) may be due to the influence of their immediate environment, known role models and the involvement of families and teachers, as well as the search for more positive and inclusive perceptions of science and technology in our lives. The present study shows the perception and motivation of secondary students and teachers toward STEM and its importance in society. Background: The low presence of students in STEM could be explained by the perception and knowledge of students and teachers toward technology. Studies show that students largely lose interest in STEM during secondary school education, and this leads to a decline in technological vocations that carries over to university and the labor market. Due to the economic and social impact of this loss, institutions are launching initiatives to support education and the development of digital competences, with special emphasis on the awakening technological vocations. Research Questions: What is the motivation and perspective of students for STEM studies? Are teachers aware of students' perceptions? What are the actions taken by teachers to encourage secondary students toward STEM? Methodology: This study follows a descriptive correlational design based on surveys (1562 students and 430 teachers) regarding issues that influence the perceptions of students and teachers toward STEM. Findings: This study demonstrates a divergence between teachers' and students' perceptions of STEM-related skills and abilities. Indeed, teachers and parents/guardians need to encourage more young people to engage in STEM activities because of the great influence they have on their decisions. The search for new STEM referents that young people can identify with is another important finding. Furthermore, this study also reveals that technology should be linked to our daily lives and emphasize its role as a social good for society. Finally, integrating STEM subjects into the curriculum and encouraging technological vocations at all stages of education are of utmost importance.